Penerapan Sanksi Hukum Terhadap Profesi Penunjang Pasar Modal Atas Informasi yang Tidak Benar dan Menyesatkan dalam Pembuatan Prospektus Menurut Undang-Undang No 8 Tahun 1995 Tentang Pasar Modal - I Gusti Agung Wisudawan (Fakultas Hukum Universitas Mataram, 2015)
The principle of openness in capital markets means that issuers and capital market supporting professionals are required to provide information about the facts materill regularly and correctly and honestly so that will affect the decisions of investors to invest in the stock market. But the reality was not as ideal as provided in the legislation sometimes issuers are trying to put pressure on the capital market supporting professionals to create beautiful prospectus as advertising on television, but if examined again bahwasannya capital market supporting professionals on the pressure of the issuer's trying to hide information the truth about the state of his company. If these continue to be allowed then of course this would be detrimental to investors or investors. Therefore professions harusbertanggungjawab capital markets and given legal sanction either criminal, civil and administrative as stipulated in Law No. 8 of 1995 on the Capital Market in order to create legal certainty, fairness and convenience of investing in the stock market.